Distance-related barriers and the internationalisation of Finnish MNES - Sarianna M. Lundan (The Research Institute of the Finnish Economy (ETLA), 2009)
In an integrated global economy, multinational enterprises (MNEs) have more opportunities than ever to reap the benefits of broader markets and more possibilities for an extensive division of labour between different locations. In spite of this, the evidence on the spread of the activities of MNEs seems to indicate a strong regional tendency, at least for the largest MNEs. This paper examines the theoretical arguments for the existence of such boundaries in an integrated global economy, and then examines their empirical importance using recent evidence on the internationalisation patterns of Finnish MNEs. We find that while some of the largest MNEs do indeed appear to be quite regional, some of the smaller internationalising firms are notably more global in terms of the spread of their activities.
Keywords: D21; D24; F21; F23; M16; 330; Multinational enterprises; internationalisation; entropy; cultural distance; institutional distance; Multinationales Unternehmen; Direktinvestition; Globalisierung; Entropie; Institutionalismus; Kulturpsychologie; Finnland